(untitled) (Confluenţe Bibliologice, 2022)
In connection with the proclamation of the National Reading Day, on February 14 in Moldova since 2022, this paper presents the arguments of psychologists and philologists, writers and poets, testifying to the beneﬁts of reading, with which the author of the article agrees. The second part of the article is devoted to the apology of reading in Muriel Barbery’s novel , The Elegance of the Hedgehog”, in which reading acts as a multi-valued symbol and motif that permeates all levels of the novel: socio-psychological, symbolic and ideological and philosophical.